Design of Driverless Pod Using Voice Commands : A Novel Approach - Bhattacharya, Swastik; Dhar, Moloy; Chanda, Srotoswini (International Journal of Computer Sciences and Engineering, 2025)
The Internet of things (IoT) refers to the concept of extending Internet connectivity beyond conventional computing platforms such as personal computers and mobile devices, and into any range of traditionally "dumb" or non-internet-enabled physical devices and everyday objects. Embedded with electronics, Internet connectivity, and other forms of hardware (such as sensors), these devices can communicate and interact with others devices over the Internet, and they can be remotely monitored and controlled. Specifically, when the automations are needed to be controlled using just voice commands from a remote location, that may be a large distance. This paper also includes detection of obstacles and the device come to a stop/waiting for the voice command from the control room (which is in remote location) and then take next decision.